2022
DOI: 10.1590/1677-5449.210011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do autocuidado com os pés entre pacientes portadores de diabetes melito

Abstract: Resumo Contexto O pé diabético é uma complicação do diabetes melito (DM), sendo a maior causa de amputação dos membros inferiores. Objetivos Avaliar a prática de medidas de autocuidado com os pés, segundo sexo e escolaridade, em pacientes portadores de DM na região nordeste no estado da Bahia. Métodos Estudo quantitativo, observacional, analítico, transversal, realizado com 88 pacientes portadores de DM, em consulta de rotina, de fevereiro a março de 2020. A coleta de dados foi executada através da aplicaçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
6
0
4
Order By: Relevance
“…É alarmante observar que muitos desconhecem os riscos associados e negligenciam medidas simples, como o uso de sapatos adequados. Diante disso, ressalta-se a urgência do letramento em saúde como ferramenta crucial para aprimorar esse autocuidado, conforme evidenciado por estudos anteriores (Lima et al, 2022).…”
Section: Resultsunclassified
“…É alarmante observar que muitos desconhecem os riscos associados e negligenciam medidas simples, como o uso de sapatos adequados. Diante disso, ressalta-se a urgência do letramento em saúde como ferramenta crucial para aprimorar esse autocuidado, conforme evidenciado por estudos anteriores (Lima et al, 2022).…”
Section: Resultsunclassified
“…After analyzing the results, it was possible to realize that 70% of people only had access to public health services, using primary care for initial care. Added to this factor, the majority of interviewees were unaware of the complications generated by DM, and 90.9% did not wear suitable shoes 11 . Even though it is a local study, it illustrates the population's lack of knowledge about DM and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several other studies from LMICs classifying footwear of people with diabetes as appropriate or inappropriate but that do not define these terms or classify more than half of their sample (and hence, were not eligible for inclusion in our study) corroborate the low rates of appropriate footwear use found in included studies. [65][66][67][68][69][70][71][72][73][74] More studies are warranted, particularly in Latin America, sub-Saharan Africa, the Middle East, Central Asia, and Eastern Europe. Little is reported in the literature about the footwear practices of people with diabetes in these regions.…”
Section: Discussionmentioning
confidence: 99%